PHOTOLYSIS OF ASCORBIC ACID IN AQUEOUS SOLUTION:A KINETIC STUDY - Iqbal Ahmad (Baqai Journal of Health Sciences)
The kinetics of photolysis of ascorbic acid in aqueous solution on UV irradiation has been studied in the pH range 1–11 and the apparent first–order rate constants for the degradation reactions have been determined. The k–pH profile for the photolysis in the acid range is represented by a sigmoid curve indicating the gradual ionization of the molecule (AH2) to ascorbyl anion (AH– ). Ascorbic acid shows maximum stability around pH 5–6 due to the lowest rate of oxidation reduction of the mono–anion form. The rate of photolysis is increased up to sevenfold at pH 10.0, compared to that at pH 5.0, due to an increase in the redox potentials with pH leading to faster oxidation of the anionic species to dehydroascorbic acid in the alkaline range. The rate is very slow in the pH range 1–2 due to the existence of the non–ionized form. The apparent first–order rate constants for the photolysis of ascorbic acid at pH 1–11 range from 0.057–3.948×10–2 min–1 . A scheme for the sequence of reactions involved in the photolysis of ascorbic acid is presented.